High Temperature Cyclic Oxidation Behaviour Ternary Ni-Al-Ti Alloys doped with Ge at 1200oC - Setiawan, Yuniarto Hendrik; Ambardi, Pradoto; Prajitno, Djoko Hadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2019)
Ni base alloys are widely used for high temperature applications, such as pressure vessel , turbine blade. Ni-base alloys possess oxidation resistance, creep resistance, fatigue resistance, the stability of the microstructure and good mechanical properties at elevated temperatures. The Ni-Al-Ti alloys were melted in a single arc melting furnace under ultra high argon atmosphere. Cyclic oxidation of the alloys was performed in air furnace at 1200 °C temperature for 25 cycles Each cycle consisted of 1 hr heating at 1200°C in an alumina tube furnace followed by 30 min cooling at room temperature. The results show that the higher addition of Ge element content can improve the mechanical properties and oxidation resistance of Ni based alloys. X-ray diffraction examination showed that the compounds were formed on the alloy after smelting Ni3Al, Ni3Ti, Ni3Ge, Ni and Ni2AlTi. While the oxide on the alloy after oxidizing to form a compounds NiO, NiTiO3, GeO2, and TiO2. In the SEM-EDS examination showed that the composition of Ge formed more dominant in the area under the element Ni oxide layer. The higher the Ge element content in the alloy has improved the resistance of the alloy indicated by the thin layer of oxide formed on the surface of the alloy.